THE FUNDAMENTAL PRINCIPLES OF OLYMPISM AS INTERNATIONAL STANDARDS OF LEGAL REGULATION OF PHYSICAL EDUCATION AND SPORTS - А. Palyukh (SUPREMANCE OF LAW, 2019)
The ideological component of the Olympic Games is based on humanism and the pursuit of peace and mutual respect among the various peoples of the world. Speaking about legal regulation in the field of sports, we first consider the basic principles of Olympism, as defined in the Olympic Charter. International law outlines the field of physical culture and sport separately and broadly, linking it with human development, tolerance and humanism, peace in the world. For the purposes of the games itself, the Olympic Charter has defi ned the principles of the Olympic Games (Olympism), as already noted earlier: Olympism - the elevation and balanced combination of qualities of the body, will and mind; sport serves the harmonious development of mankind, the peaceful existence, the preservation of human dignity; olympic movement; practice of sport is a human right; political neutrality; prohibition of discrimination. Determination of the prohibition of discrimination as the main principle of Olympism is positive in the context of the general fight against discrimination. Olympic games attract people around the world, successful athletes are the authority for the spectators. To overcome the phenomena of discrimination, the basic ideological component remains the main in the modern world, since whatever legal mechanisms of protection of rights would not build the state, the main guarantee of observance of human rights is to increase the level of legal awareness.